2004
DOI: 10.1074/jbc.c400283200
|View full text |Cite
|
Sign up to set email alerts
|

Dimer Dissociation Is Essential for Interleukin-8 (IL-8) Binding to CXCR1 Receptor

Abstract: Chemokines play a fundamental role in trafficking of immune cells and in host defense against infection. The role of chemokines in the recruitment process is highly regulated spatially and temporally and involves interactions with G protein-coupled receptors and cell surface glycosaminoglycans. The dynamic equilibrium between chemokine monomers and dimers, both free in solution and in cell surface-bound forms, regulates different components of recruitment such as chemotaxis and receptor signaling. The binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
90
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(95 citation statements)
references
References 24 publications
(25 reference statements)
5
90
0
Order By: Relevance
“…Residues in the N-terminal domain (binding site-I) and in extracellular loops (binding site-II) of CXCR1 interact with IL-8 (13,14,16,(30)(31)(32)(33)35,66,68,69). Specific residues in the N-terminal domain of CXCR1 contribute to both the selectivity and the affinity of the receptor for IL-8.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Residues in the N-terminal domain (binding site-I) and in extracellular loops (binding site-II) of CXCR1 interact with IL-8 (13,14,16,(30)(31)(32)(33)35,66,68,69). Specific residues in the N-terminal domain of CXCR1 contribute to both the selectivity and the affinity of the receptor for IL-8.…”
Section: Discussionmentioning
confidence: 99%
“…Although IL-8 exists as a homodimer in solution (8), monomeric IL-8 has been shown to bind to CXCR1 with similar or higher affinity than the dimer (13,14). Truncation of the last six C-terminal residues results in a stable monomeric form of IL-8 (1-66) (34).…”
Section: Immobilization Of Il-8 Bound To Cxcr1 In Phospholipid Bilayersmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study indicated that the protein sequence of CXCR1 is conserved in the transmembrane and intracellular domains but less conserved in the extracellular domains (Rajagopalan and Rajarathnam 2004). The binding of IL-8 involves close interactions between the CXCR1 N-domain and IL-8 N-loop residues and between CXCR1 exoloops and the transmembrane and IL-8 N-terminal residues (Fernando et al 2004;Rajagopalan and Rajarathnam 2004). Both the sliding window analysis and the codon-based neutrality test tend to favor positive selection acting on the N-terminal domain of human CXCR1, the critical region for ligand/receptor signaling for neutrophils.…”
Section: Resultsmentioning
confidence: 99%